PERANAN ORANG TUA DALAM MENGUATKAN MORAL ACTION PADA ANAK DI DESA WIROGUNAN KECAMATAN KARTASURA KABUPATEN SUKOHARJO - Suyahman, Suyahman (FPIPSKR Universitas PGRI Semarang, 2023)
Abstract. This study aims to describe the role of parents in strengthening moral action in children in Wirogunan village, Kartasura District, Sukoharjo regency. This type of research is qualitative research. The research subjects were parents and their children who lived in Wirogunan village, Kartasura sub-district, Sukoharjo regency, and the object was moral action. Methods of collecting observational data, interviews and documentation. The validity of the data is done by triangulating sources and methods. The data analysis technique was carried out with an interactive flowing technique consisting of 4 steps: data collection, data reduction, data display and data verification. The results of the study based on field observations made on 2-5 November 2019 found the following things: many behaviors that deviate from moral values by teenagers in Wirogunan village, Kartasura District, Sukoharjo Regency, including: promiscuity , alcohol, gambling, fighting, brave with parents, disrespectful with parents, opening pornographic sites and action porn on his cellphone and using illegal drugs. parents do neglect their children, parents less attention and care for their children. The conclusion is that due to lack of parents' attention to their children, there are many violations of moral action on children in Wirogunan Village, Kartasura District, Sukoharjo Regency.